PENGARUH DIFERENSIASI KUALITAS AUDIT, KESULITAN KEUANGAN PERUSAHAAN, OPINI AUDIT, KEPEMILIKAN INSTITUSIONAL, DAN FEE AUDIT TERHADAP PERGANTIAN KAP (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2013) - Fajrin, Febrika; -, Kennedy; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aim to examined the influence of the differentiation of audit quality, financial distress, audit opinion, institutional ownership and audit fee to auditor switching. This research is expected to be a reference for the stakeholders to look at the motivation of management to maintain or make the auditor switching. The sample used in this study are manufacturing companies listed on the Indonesia stock exchange in the period 2011-2013. Total sample in this research 132 companies using purposive sampling.Companies that a sample of this is the company that contains information that covers all operational definition of research, namely: the company decreased audit quality (affiliated Big 4), the company is experiencing financial distress, giving an unqualified audit opinion, institutional ownership of the company, and fee audit. Data were analyzed using logistic regression (logistic regression) with the help of a computer program SPSS version 17.0. Results of this research are that institutional ownership dan audit fee has significant effect on auditor switching. While other factors like the differentiation of audit quality, financial distress, and audit opinion do not have significant effect on auditor swithing.Keywords: audit switching, differentiation of audit quality, financial distress, institutional ownership, audit fee.